GOLDMAN’S PLURALISTIC APPROACH TO AESTHETIC EXPERIENCE AND PIET MONDRIAN’S INTUITIVE NEO-PLASTIC ART: Received: 16th April 2022; Revised: 13th June 2022, 30th June 2022; Accepted: 30th June 2022 - Fallahzadeh, Ali; Rahbarnia, Zahra (PEOPLE: International Journal of Social Sciences, 2022)
The objective of this article is to demonstrate the credibility of the pluralistic approach to aesthetic experience, mainly focused on Goldman's recent argument, in the case of Neo-Plastic paintings which is chosen as the most mature paradigm of pure abstract art created based on the premises of formalism. This article tries to clarify whether the spectator should realize the aesthetic value of pure abstract art based on a formalistic standpoint (as it has been commonly used), or a pluralistic mode: interactive and simultaneous involvement of all mental faculties namely perception, imagination, emotion, and cognition. To achieve the goals of this article, Mondrian's writings will be examined in light of two different viewpoints: formalists’ intuitive approach and Goldman’s pluralistic approach. At the end of this article, it becomes evident that although Mondrian, in several instances in his writings emphasizes the role of intuition in the creation and aesthetic perception of spiritual content (universal beauty as truth) of his Neo-Plastic art, his approach to aesthetic experience, similar to the recent argument of Goldman, is pluralistic; meaning that for appreciation of the aesthetic value of Neo-Plastic paintings all mental faculties, except imagination, are correlatively involved.